2019
DOI: 10.12669/pjms.35.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific impairment of Lung Function on Spirometery in Patients with Chronic Hepatitis-C

Abstract: Objectives: To document frequency of non-specific impairment of lung functions (NILF) in patients of HCV and to compare according to gender, genotype, liver fibrosis score and smoking status. Methods: Patients of chronic hepatitis C were included after informed consent. Demographic data was recorded, and they underwent baseline investigations, fibroscan, abdominal ultrasound and PFT. Patients were segregated on basis of gender, fibroscan stages and smoking status. NILF was labelled if any two of three cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Notably, in some studies, these dysfunctions were shown to be associated with the severity of liver cirrhosis, as assessed by various scores, such as the Child Pugh Score and the Model for End-Stage Liver Disease (MELD) score, clinical characteristics such as ascites and laboratory parameters such as albumin ( 11 , 13 , 19 , 20 , 23 , 26-28 , 32 , 33 , 35 , 36 , 40 ). Some studies ( 19 , 20 , 23 , 33 , 35 ) have found a significant association between decreasing PEFR, FVC, FEV1 and FEF25-75% values, and increasing ascites.…”
Section: Spirometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, in some studies, these dysfunctions were shown to be associated with the severity of liver cirrhosis, as assessed by various scores, such as the Child Pugh Score and the Model for End-Stage Liver Disease (MELD) score, clinical characteristics such as ascites and laboratory parameters such as albumin ( 11 , 13 , 19 , 20 , 23 , 26-28 , 32 , 33 , 35 , 36 , 40 ). Some studies ( 19 , 20 , 23 , 33 , 35 ) have found a significant association between decreasing PEFR, FVC, FEV1 and FEF25-75% values, and increasing ascites.…”
Section: Spirometrymentioning
confidence: 99%
“…Of note, in a study evaluating the presence of non-specific impairment of lung functions (NILF), defined as the observation of any two of three following criteria: i) FVC <80% of predicted; ii) FEV1 <80% of predicted; iii) FEV1/FVC ≥70, NILF was statistically associated with the female sex and with increasing FibroScan scores ( 40 ).…”
Section: Spirometrymentioning
confidence: 99%
See 1 more Smart Citation
“…A similar association (relative risk of 1.8) was found using the DTB. Several studies evaluated the impact of HCV infections on the development of COPD, with divergent conclusions as whether HCV is directly involved in the pathogenesis of COPD [34][35][36][37][38][39]. While most studies discussed HCV as a risk factor for the development or exacerbation of COPD, Fischer and colleagues report that HCV is not an independent risk factor for obstructive lung disease [37].…”
Section: Plos Onementioning
confidence: 99%
“…In southern Taiwan, hepatitis C virus ( HCV) is endemic, and it has been shown to lead to dysmetabolic syndrome 12 with hypocholesteremia, hepatic steatosis, and large abdominal girth, which are risk factors for iPF. 13, 14 Chronic HCV infection has also been associated with a worse prognosis in asthmatic patients 15 and chronic obstructive pulmonary disease. 16 The additional influence of HCV on lung function decline 17 has been associated with pulmonary fibrosis 18 and reduced lung capacity through immune-mediated reactions.…”
Section: Introductionmentioning
confidence: 99%